Relationship of telomere length in colorectal cancer patients with cancer phenotype and patient prognosis - Kroupa, Michal; Rachakonda, Sivarama Krishna; Liska, Vaclav; Srinivas, Nalini; Urbanova, Marketa; Jiraskova, Katerina; Schneiderova, Michaela; Vycital, Ondrej; Vymetalkova, Veronika; Vodickova, Ludmila; Kumar, Rajiv; Vodicka, Pavel (British journal of cancer, 2019)
BACKGROUND: Telomeres, repetitive DNA capping ends of eukaryotic chromosomes, are important in the maintenance of genomic integrity. Perturbed telomeres are common features of many human malignancies, including colorectal cancer. METHODS: Telomere length (TL), measured by a Monochrome Multiplex Real-Time qPCR, was investigated in tumour tissues, adjacent mucosa, and blood from patients with colorectal cancer with different clinicopathological features and its impact on patient survival. TL was also measured in a limited number of liver metastases, non-cancerous liver tissues or corresponding tissues from the same patients. RESULTS: TL in tumour tissues was shorter than in the adjacent mucosa (P < 0.0001). Shorter TL was observed in tumours with lower stage than in those with advanced stages (P = 0.001). TL was shorter in tumours at the proximal than at the distal sites of the colon (P < 0.0001). Shorter TL was also associated with microsatellite instability (P = 0.001) and mucinous tumour histology (P < 0.0001). Patients with a smaller TL ratio between tumour tissues and the adjacent mucosa were associated with increased overall survival (P = 0.022). Metastasised tumours had shorter telomeres than the adjacent non-cancerous liver tissues (P = 0.0005). CONCLUSIONS: Overall, the results demonstrate differences in TL between tumours and the adjacent mucosa, between tumours located at different sites and association with patient survival.
Keywords: lidé; Middle Aged; Adult; Prognosis; prognóza; lymfatické metastázy; fenotyp; Female; Microsatellite Instability; telomery; Phenotype; Humans; lidé středního věku; mužské pohlaví; Lymphatic Metastasis; kolorektální nádory; ženské pohlaví; Colorectal Neoplasms; Aged, 80 and over; senioři nad 80 let; Male; Aged; Telomere; mikrosatelitní nestabilita; dospělí; senioři